Keefektifan Model Pembelajaran Problem Based Learning Berbantuan Media Lakerlok terhadap Hasil Belajar IPAS Peserta Didik Kelas VI SDN Tambirejo Demak - Rizqi Dian Yulia Putri; Erik Aditia Ismaya; Much Arsyad Fardani (Mataram University, 2026)
Low learning outcomes in Natural and Social Sciences (IPAS) at the elementary school level remain a challenge requiring attention, as instruction often fails to actively involve students in the problem-solving process. Therefore, instructional innovations capable of enhancing student engagement are needed; one such approach is the implementation of a problem-based learning model supported by lakerlok media.This study aims to determine the effectiveness of problem-based learning models and Lakerlok media in improving elementary school students' learning outcomes. This study used a pre-experimental design with a one-group pretest-posttest approach involving 20 sixth-grade students of SDN Tambirejo Demak as subjects. The data collection techniques tested used normality tests, paired sample t-tests, and N-Gain tests. The results of the data normality test were carried out using Shapiro-Wilk and showed that the data were normally distributed, with pretest and posttest significance values greater than 0.05. Furthermore, the paired sample t-test produced a sig. (2-tailed) value of 0.000 <0.05, so Ho was rejected and Ha was accepted, which means there was a significant difference between the pretest and posttest results. The average student score increased from 31 to 80 with an N-Gain Score of 0.6660 in the moderate category, the highest score being 90 and the lowest being 11. Thus, the problem-based learning model and Lakerlok media proved to be quite effective in improving the learning outcomes of Science.